Kitābat al-Baḥth al-ʻIlmī fī al-Siyāsah al-Sharʻiyyah Khiṭṭah wa Ṣiyāgah - Amany Burhanuddin Umar Lubis (Fakultas Dirasat Islamiyah, Univitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2005)
The writing of research results or scientific papers in the field of siyasah syar 'iyyah must be in line with the mastery of steps, forms and methods. In this article, the author manages to explain these three aspects, which includes the title selection technique, the procedures of expressing the essence of research consisting of introduction, chapters of discussion and closing along with attachments. In addition, the writer also describes in detail some of the important points that must be included after expressing the essence of research, such as interpreting the result obtained from the research, providing suggestion and recommendation regarding the results obtained, proposing a research or further studies related with the discussed theme.